Strategy of delayed surgery for ventricular septal perforation after acute myocardial infarction. Issue 5 (May 2018) - Furui, Masato; Yoshida, Takeshi; Kakii, Bunpachi; Uchino, Gaku; Nishioka, Hiroaki
Highlights: Improve the results of ventricular septal perforation (VSP) surgery. Operations for 24 patients with VSP were withheld during the acute phase of acute myocardial infarction. The 30-day mortality rate improved as 4.2% compared with that in previous studies. Organ function was not worsened by delaying the surgery. Withholding operation may decrease VSP mortality; delayed surgery may be beneficial. Abstract: Background: The timing of surgical repair for ventricular septal perforation (VSP) is important because patients are susceptible to bleeding from fragile myocardial tissue or residual shunt during the acute phase of acute myocardial infarction (AMI). This study aimed to assess the results of delayed surgery for VSP performed 2 weeks after AMI. Methods: In total, 24 consecutive postinfarction patients with VSP (mean age: 72.6 ± 10.4 years; 13 males) underwent operation between May 2003 and June 2016. We postponed surgery during the acute phase and performed an elective surgery if the patient could wait for 2 weeks with support from intra-aortic balloon pumping (IABP) and respiratory management. If we could not control heart failure and organ function worsened during that period, we performed emergency surgery. Postoperative outcomes included complications, 30-day mortality rate, long-term hospital death, reoperation rate, and risk factors for hospital mortality. We examined whether organ function was maintained by delaying the surgery. Results: Of the 24 patients, 11 (45.8%) required emergency surgery, and 13 (54.2%) could wait 2 weeks for surgery. The average time from AMI onset to diagnosis of VSP was 4.5 ± 1.6 days, and the average time from VSP diagnosis to surgery was 9.0 ± 6.0 days; 5 patients (20.8%) required resurgery for VSP due to residual shunt, recurrent VSP, or pseudoaneurysm of the left ventricle. The 30-day mortality rate was 4.2% (1 patient), and long-term hospital mortality rate was 12.5% (3 patients). Organ function was maintained in 10 patients (76.9%) who underwent elective surgery, and organ dysfunction was not advanced by delaying the surgery. Conclusions: We could delay surgery for an average of 9 days from VSP onset by means of IABP or respiratory management without the deterioration of organ function. The 30-day mortality and long-term outcome were favorable.